THE LOCAL WISDOM OF THE TELUK NAGA COASTAL COMMUNITY, TANGERANG IN THE CREATIVE WORK OF THE SONG KRAMAT KAREM GAMBANG KROMONG - Malona Sri Repelita (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Kramat Karem is one of the repertoires of Gambang Kromong songs whose lyrics describe the historical eruption of Mount Krakatau in 1883. To understand natural disasters, apart from weather forecasts, people need to understand the local wisdom of their ancestors in preserving nature. After the eruption which created the tsunami at Jakarta and Lampung, the ancestors of Betawi felt the need to share these historical events in saga stories and traditional songs. The song's lyric contains local wisdom regarding natural events and is passed on to the next generation to preserve nature in everyday life. Unfortunately, these days only a few can understand such songs. This study aims to examine the relationship of the text in a cultural context and the function of socializing local wisdom through the song. This research uses qualitative methods so that naturalistic, basic, and profound things can be obtained more accurately. The data collected through literature studies, interviews and observations in the community were analyzed using ethnomusicological theory and social anthropology, which help analyze the function of music in a cultural context. This study is expected to produce recommendations for coastal communities to appreciate and pay close attention to natural phenomena through local wisdom in the song Kramat Karem. In addition, the results of this study also become a trigger and impetus for local communities to strengthen traditional music as a medium of communication and socialization of local wisdom.